Cultural Phenomenon Of Tiktok As A New Form Of Communication Among Teenagers - Kencana Putri, Mona; Narti, Sri; Maryaningsih, Maryaningsih (Multidisciplinary Journals, 2024)
TikTok is an audiovisual media that spreads various creativities and uniqueness, allowing for voice recording, adding background sound, videos, and collaborations. The phenomenon is nothing but a fact realized and entered into human understanding. Phenomenology aims to study how phenomena are experienced in consciousness, thoughts, and actions, such as how the phenomena are valued or accepted ethnically, because the phenomenon itself is nothing but a fact realized and entered into human understanding. The TikTok cultural phenomenon as a new form of communication among teenagers illustrates significant changes in how teenagers interact, express themselves, and shape their identities in the digital era. Through a phenomenological approach, the research results show that TikTok users vary greatly, including creative expression, entertainment, social interaction, popularity achievement, and education. TikTok users' actions include content creation and consumption, social interactions, participation in trends, and information seeking. There is a need to delve deeper into how TikTok users perceive and interpret experiences through modifying categories based on the findings of each in-depth study.